FITOREMEDIATION EFFECTIVENESS OF LIQUID WASTE BATIK INDUSTRY WITH GENGER PLANT (Limnocharis flava) - Utami, Yanika Cahya; Aminatun, Tien (Universitas Negeri Yogyakarta, 2024)
This study aims to 1) determine the effectiveness of genjer plant (Limnocharis flava) as a phytoremediator of batik industrial wastewater seen from the parameters of BOD, COD, TSS and pH, and 2) determine the performance of genjer plant (Limnocharis flava) as a phytoremediator of batik industrial wastewater. seen from the morphology. This research is an experimental study with a composite sample technique. The results showed that, 1) phytoremediation of batik liquid waste was found to be effective in reducing the value of BOD, COD in the 75% dilution treatment with a reduction efficiency of 98.71% and 96.45%, respectively. The most effective decrease in TSS value was at 25% dilution with a reduction efficiency of 92.27%. The pH value after treatment changed to neutral, 2) the performance of genjer (Limnocharis flava) showed a change in both color and growth. Symptoms that arise are leaves and stems turn yellow, chlorosis appears, to indicate a state of necrosis. Although some plants die, genera plants can still live by forming new plant shoots.Keywords: effectiveness; phytoremediation; chlorosis; batik industry liquid waste; Lymnocharis flava